Can governance mechanisms minimize agency costs? - Linda, Linda; Saputra, Mulia; Fuadi, Raida; Fadhlia, Wida (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this research is (1) to know whether agency costs incurred in companies listed on IDX 30 are of high or low value? (2) The aim is to investigate how agency costs are affected by different corporate governance mechanisms, specifically the size of the board of directors, the size of the board of commissioners, and the size of the audit committee. This research employed quantitative methods through a comprehensive review of existing literature and the subsequent formulation of hypotheses. In this study, agency costs are proxied by expense comparison and the capital utilization comparison. The results show most of companies listed on IDX 30 have low agency cost. The expense comparison indicates that the size of the board of directors has a notable impact on reducing agency costs. On the other hand, the capital utilization comparison shows that the size of the board of commissioners has a significant influence in reducing agency costs. However, the size of the audit committee does not seem to have a substantial effect on agency costs. Low agency costs that occur indicate low agency conflicts that occur - so this firm can list on IDX 30.